Long-term evolution of an inner bar at the mouth of a microtidal river. (5th November 2021) - Baldoni, Agnese; Perugini, Eleonora; Soldini, Luciano; Calantoni, Joseph; Brocchini, Maurizio
Abstract: We conducted, for the first time, a study of the long-term evolution of an inner mouth bar in a microtidal environment that complements field observations with detailed numerical modelling of the same morphodynamics. Images collected by a video-monitoring station, from 2016 to 2019, were processed to study the evolution of a persistent inner mouth bar formed inside the highly engineered Misa River estuary (Senigallia, Italy) after years of reduced precipitation and discharges. We developed a semi-automatic procedure to detect the emerged area of this deposit. We seek to quantify the relationship between the long-term evolution of the bar and the forcing from the river, waves and tides. The observed high peaks in river discharge caused a strong downriver bar migration (i.e. almost twice the river width). Conversely, the observed sea storms produced an upriver bar migration smaller than one river width. A much slower and weaker (less than half the river width) upriver migration was also observed during periods of large area accretion and due to mild wave climate. Moreover, results showed that the sea water level variation did not directly impact the morphodynamics of the estuary, affecting the emerged portion of the bar only. Numerical simulations, run with Delft3D, were used to complete the information coming from field observations. After some checks on the proper use of the solver for the scenarios and environments of interest, some parametric simulations were run to highlight the role of the different forcing on the bed evolution. Simulations showed, as expected, erosion of the riverbed and significant downriver migrations (four river widths) during peaks of river discharge comparable to the 1-year return period discharges. Numerical results also showed upriver sediment transport when the wave forcing was dominant, with 10-years return period waves inducing an upriver bar migration in the order of one river width. Then, one real-life event was simulated to inspect the interaction of the various forcing and to compare their effects with the observations. Our analysis provides new insight into the complex morphodynamics in a microtidal estuary when weak river discharge is opposed by sea waves driving upriver sediment transport. A more thorough understanding of the morphodynamics is needed for future forecasting of the formation and evolution of sediment deposits inside estuarine channels that can inhibit both navigation and the flux of sediment from the river to the estuary. Highlights: Detection of an inner bar at the mouth of a microtidal river from images acquired by a video-monitoring station. Correlation of the bar area evolution and centre of mass migration with the estuarine forcings. Field observations show the effect of different combinations of river flows and waves on the evolution of the bar. Parametric simulations show that, at a given return period, the river discharge caused a larger bar migration than sea waves. A real-life numerical simulation displays evolution behaviours in agreement with field observations.